Optimized Climate Change Management: Integrating Fuzzy CRITIC-TOPSIS Approach with Continuous Function-Valued Fuzzy Sets - Ünver, Mehmet; Aydoğan, Büşra (Risk Assessment and Management Decisions, 2025)
Climate change is a worldwide issue that affects the entire planet, necessitating comprehensive management planning and the development of effective solutions. Given the subject’s worldwide relevance, the procedures should produce fast and accurate findings. Given all of these issues, effective climate change management plans and assessment criteria should be developed, backed up by the appropriate theoretical components, and finished with analysis methods. This study is based on genuine facts. Expert opinions inform the development of climate change evaluation criteria and strategies for climate change management. Each alternative is assessed using all criteria, and a multi-criteria group decision-making problem is created. In the theoretical dimension, the decision problem is helped by continuous function-valued q-rung orthopair fuzzy sets (CFV-q-ROFSs) and a novel cosine-based distance measure. The use of CFV-q-ROFSs and the new distance measure across these fuzzy sets leads to a more accurate evaluation. Criteria Importance The Intercriteria Correlation (CRITIC) approach and the approach for Order of Preference by Similarity to Ideal Solution (TOPSIS) are then united to propose an extended and combined fuzzy method. The criteria are weighted using the CRITIC method, and the alternatives are prioritized using TOPSIS. TOPSIS employs the approved innovative distance measure to calculate the distance between alternatives. A comparison of six techniques is performed to ensure that the results are consistent.